Evaluasi Kualitas Layanan M-Banking BRI - Mochammad Khoirul Zidan; Nursya’bani Purnama (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the extent to which service quality influences customer satisfaction and loyalty among users of the BRImo mobile banking application at Bank Rakyat Indonesia (BRI). In the era of rapid digitalization, technology-based banking services have become a strategic innovation to enhance customer convenience and trust, where service quality plays a crucial role in shaping the user experience. The research adopts a quantitative associative/verificative approach using a survey method involving 102 respondents who are active BRI customers in the Yogyakarta region. Data were collected through the distribution of questionnaires using a Likert scale, and then analyzed using SPSS software through validity and reliability tests, multiple linear regression analysis, as well as t-tests and F-tests. The results of the analysis show that service quality has a positive and significant effect on customer satisfaction among BRImo application users. In addition, service quality is also proven to have a direct influence on customer loyalty. This means that the higher the quality of digital services provided by BRI, the greater the increase in customer satisfaction and loyalty towards the application. The findings of this study emphasize that reliability, responsiveness, security assurance, and empathy are essential elements in building long-term loyalty in digital banking services